Distinguen objetos de su entorno cuerpos geométricos - Llacsahuanga Cordova, Carla Janet (2018)
In the present study, the research was directed towards the investigation of new methodological skills that have a visible impact on the process of acquiring knowledge in this discipline, pointing out causes that prevent magnificent products, both when giving advice by the teacher and when collecting new concepts by the student. In the learning process, the dilemmas related to the acquisition of new knowledge about mathematics, which originate in the various procedures used during the pedagogical practice, is the lack of motivation of the students in their cognitive process of the area and in the implementation lack of new strategies aimed at the dynamization of mathematical knowledge from the classroom, considering its importance for the integral formation of the individual. The first chapter of the research is centered and identify competencies, capacities and indicators that are developed on the design of the implemented session and in the second chapter we identify pedagogical theoretical support that sustains the teaching practice by analyzing the pedagogical processes that are developed during the learning session and finally from the analysis and interpretation of the results we have formulated the conclusions, recommendations, bibliographical reference and annexes to corroborate the researched. format of publication authorization.